A study of Gamow-teller strength using the 208Pb(p,n) and 181Ta(p,n) reactions at intermediate energy, Ep=122 MeV - Tshivhase, Victor Makondelele (Department of Physics, 2016)
Bibliography: p. [105] - 112.